ANALISIS TINGKAT KEPUASAN MENGGUNAKAN SKALA LIKERT PADA LAYANAN SPEEDY YANG BERMIGRASI KE INDIHOME - Edi Suwandi . (Faculty of Engineering, Universitas Tanjungpura, 2019)
Consumer satisfaction is the level of one's feelings after comparing (performance or results) that is felt compared to expectations. The purpose of this study in general is to determine the level of customer satisfaction Speedy Internet and Indihome Internet . This research was conducted in the city of Pontianak, the method used in this study was deskrip tif and comparative methods using questionnaires by going down the field and conducting interviews with speedy internet consumers who migrated to Indihome. Sessionary scale calculations using a Likert Scale, Validity Test (T-count, T-table) and Reliability Test, to find out the results of the comparison of the level of Speedy Internet satisfaction and Indihome internet. As the result of the calculations obtained by using Likert scale level of customer satisfaction and Indihome Speedy internet for very dissatisfied percentage was 0%, the percentage of Internet Speedy disgruntled Indihome 11.77% 5.88% Percentage of Internet Speedy satisfied 70 , 58% Indihome 64.70%, and the percentage of Speedy Internet that felt very satisfied was 17.64%, Indihome was 29.41%.